Paradigma Berbasis Bukti dalam Kewirausahaan: Analisis Kualitatif atas Praktik Meta-Analisis dan Standar Pelaporan Akademik - Moh Trisamanta; Moh Zalmi Kahardani; Erwin Santosa (Studia Ekonomika, 2026)
This qualitative literature review explores the emergence of evidence-based paradigms in entrepreneurship research by analyzing the role of meta-analytic practices and academic reporting standards. Drawing on recent scholarly contributions, the study examines how systematic reviews and meta-analyses contribute to the accumulation of robust, generalizable knowledge in entrepreneurship. It also investigates the influence of frameworks such as PRISMA and APA's Journal Article Reporting Standards (JARS) on methodological transparency and replicability. Findings reveal that while meta-analysis offers significant insights, its rigor depends on adherence to evolving reporting protocols and quality assessment tools. The review highlights gaps in current practices, particularly related to publication bias, heterogeneity, and ethical transparency. It calls for enhanced integration of evidence-based principles to strengthen the bridge between academic knowledge and entrepreneurial practice.